Aqueous Lithium-Ion Batteries Using O2 Self-Elimination Polyimides Electrodes. Issue 10 (1st January 2015) - Chen, Long; Li, Wangyu; Guo, Zhaowei; Wang, Yonggang; Wang, Congxiao; Che, Yong; Xia, Yongyao
Abstract : Lithiated negative electrode materials (in discharge state) in aqueous solutions could be oxidized in the presence O2 and H2 O, resulting in their poor charge/discharge cycle life. In the present work, we reported that lithiated polyimide can be oxidized by O2 in aqueous solution without much negative effect on its charge/discharge cyclability. The lithiated polyimide is converted to the almost identical polyimide structure by O2 oxidation in the aqueous solution based on FTIR spectra (O2 self-elimination performance). We also confirmed the good charge/discharge voltage profile and capacity of polyimide as an anode material in aqueous solutions. A sealed polymide-AC/LiNO3 /LiMn2 O4 aqueous LIB exhibited excellent cycle life with a capacity retention above 95% after 1000 charge/discharge cycles on 2C rate (charge/discharge) at room temperature, even when the battery was overcharged once after the 50th cycle.